Pengaruh Tipe Kepribadian Auditor dan Budaya Organisasi terhadap Perilaku Disfungsional Audit - Nadiah Zahra; Hajan Hidayat; Adhitomo Wirawan (Politeknik Negeri Batam, 2020)
This study aims to determine whether there is influence personality type A auditor and organizational culture on audit dysfunctional behavior. The method used was a survey using a questionnaire of 34 respondents who were auditors at 5 public accounting firm Batam. The research hypothesis was tested using a multiple regression analysis. This study uses primary data in the form of a questionnaire with a 5-point Likert scale. The auditor's personality type is measured by ambitious, competitive, and achievement-oriented attitudes. Organizational culture variables are measured by the ethical attitudes that exist in an organization. The results revealed that there was no effect between auditor A personality type and organizational culture on audit dysfunctional behavior. Future studies can add other variables and enlarge the population area.